The therapeutic role of mental health nurses in psychiatric intensive care: A mixed‐methods investigation in an inner‐city mental health service. Issue 7 (29th June 2017) - McAllister, S.; McCrae, N.
Accessible summary: What is known on the subject?: Mental health services have been radically transformed since the 1990s, with an emphasis on care in the community. However, acute psychiatric wards remain an important component of service provision. Research shows that patients receive limited therapeutic interaction with nurses in such settings. A recent review showed that just 4%‐12% of nurses' time was spent on activities that could be considered therapeutic. What this study adds to existing knowledge?: Whereas nurses wanted more time for individual therapeutic activity, patients were content with brief interactions. However, such contact was not always available, partly due to workload pressures. Both nurses and patients believed that a collaborative approach, involving the whole multidisciplinary team, was key to the success of therapeutic engagement. The meaning of therapeutic engagement remains nebulous. What are the implications for practice?: Nurse education, ward management and clinical supervision should have greater emphasis on therapeutic engagement. Further research is needed to develop therapeutic engagement in acute psychiatric settings; such work should involve patients as active and equal partners. Abstract: Introduction: Despite indications that therapeutic interaction is beneficial for patients and for nurses' job satisfaction in acute psychiatric care, research shows a small amount of nurses' time is spent on such activity. Aims: This study investigated the actual and potential therapeutic role of the mental health nurse in psychiatric intensive care, where admission is due to violence or aggression. Methods: In a mixed‐methods concurrent triangulation design, clinician and patient activity was observed using a structured measurement tool, and qualitative interviews were conducted with four practitioners and six patients. Findings were generated using thematic analysis and descriptive statistics. Results: Of the directly observed 234 clinician and 309 patient activities, 20.9% and 15.9%, respectively, were classified as therapeutic engagement. Interviews revealed that both clinicians and patients wanted more therapeutic contact, but whereas nurses wanted longer time to spend in individual sessions, patients preferred brief but more frequent interaction with nurses. Discussion: This study shows disparity between actual and desirable levels of therapeutic interaction. Apart from organizational constraints, a fundamental problem is the lack of definition or established practices of therapeutic engagement. Implications for Practice: There should be more emphasis on therapeutic engagement in nurse education, ward management and clinical supervision.